Bearing fruit or falling flat? The story of contract farming in India - A G Adeeth Cariappa; Manjisha Sinha; Sheela Kharkwal; Apoorva Srinivas (Agricultural Economics Research Review, 2023)
Contract farming (CF) holds potential to stimulate demand-led agricultural growth in India. CF is practiced by 5.5 lakh farmers. Government of India’s 2020 CF law was withdrawn after extensive farmer protests. We scrutinize CF’s empirical evidence, highlight research gaps, and discuss policy implications. Meta-analysis indicates CF can decrease input costs by 28%, improve productivity by 20%, and boost profits by 51%. Notably, outcomes like educational progress, nutritional security, gender equity, social inclusion and sustainability remain under-researched.